Analisis Distribusi Serangga Tanah Jalan MT Haryono dan Tlogomas Malang - Hasan Zayadi; Nurul Jadid Mubarakati (Biota, 2017)
Vegetation in urban areas can be viewed, as compensation for environmental change due to urbanization of plant diversity affecting the diversity of animals in an ecosystem, the loss of plant species will disrupt the food webs in the ecosystem. Research on the diversity of soil insects found in shade trees species is still not widely done. The purpose of this study were to identify the types of soil insects found in shade trees along Dinoyo and Tlogomas roadside in sub-district of Lowokwaru, Malang and to characterize spatial distribution of soil insect species found in shade trees along Dinoyo and Tlogomas roadside in sub-district of Lowokwaru Malang by using GIS application. Sampling was conducted at two different locations (MT Haryono and Tlogomas Road). Soil insect analysis was calculated using Shannon-Wiener (H') index at different sites. Variables measured were Relative Frequency (FR) and Relative Abundance (KR), while mapping Spatial descriptions. Distribution of soil insects was done by stages in spatial data analysis including digitization, attribute data, map overlay, and map output results. The results of this study obtained the number of species of soil insects as many as 14 species with a total of 287 individuals. Soil insects most commonly found were family Formicidae, the species of Momorium destructor with the number of individuals as much as 87 individuals, and Paratrechina longicornis as many as 86 individuals.